THE INFLUENCE OF THE GUIDED INQUIRY LEARNING MODEL ON STUDENTS"™ MATHEMATICAL REFLECTIVE THINKING ABILITY - Lorenza, Dela Alifa; Nurhanurawati, Nurhanurawati; Setiawati, Santy (Jurnal Pendidikan Matematika dan IPA, 2025)
Mathematical reflective thinking ability is a thinking ability that involves the process of connecting existing knowledge with new knowledge to solve problems by identifying problems, evaluating, concluding, and making decisions to find the best solution to the problems faced. Mathematical reflective thinking ability has an important role for teachers and students in mathematics learning that focuses on problem solving. However, in reality, many students still have difficulty reflecting on their thinking processes when solving mathematical problems. Therefore, it is necessary to implement a learning model that actively involves students in activities and focuses on solving mathematical problems, one of which is the guided inquiry model. The purpose of this study was to determine the effect of the Guided inquiry learning model on students' mathematical reflective thinking abilities. The research method used was a quasi-experimental study. The population in this study were all eighth-grade students of SMP Negeri 7 Bandar Lampung in the even semester of the 2024/2025 academic year with a sample of 30 students in grades VIII.8 and VIII.9 selected using a purposive sampling technique. The research design used was a posttest only control group design. The data in this study were quantitative data obtained from a mathematical reflective thinking ability test. Data analysis in this study used a statistical test, namely the t-test. The results showed that the mathematical reflective thinking ability of students who followed the guided inquiry learning model was higher than the mathematical reflective thinking ability of students who followed conventional learning. Thus, the guided inquiry learning model influenced students' mathematical reflective thinking ability.